Dispensasi Perkawinan di Pengadilan Agama Bandung Pasca Undang-Undang No.16 Tahun 2019 - Neneng Resa Rosdiana; Titin Suprihatin (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Judging from the case data of the Bandung Religious Court, it can be seen that there was a spike in marriage dispensation cases in 2019. In the same year the government has passed Law No. 16 of 2019 concerning Marriage, in which the regulation is the result of a revision of Law No. 1 of 1974. The change was justified because the age provision in the previous regulation was deemed to discriminate against women. Where in the cloud women can only marry when they are 16 years old while men are 19 years old. So that in Law No. 16 of 2019 the provisions were changed, women and men are allowed to marry if they have reached the age of 19 years. The purpose of this study was to find out what the judges considered in granting marriage dispensation cases at the Bandung Religious Court when the government tightened the age of marriage with the ratification of Law No. 16 of 2019. The research that the author did was descriptive research with empirical juridical research methods, data sourced from case reports and regulations regarding the age of marriage in Law No. 16 of 2019, using data collection techniques through interviews and library research. The results of this study indicate that the judge by looking at the facts that occurred in the trial mostly used considerations of the benefit of the parties. Abstrak. Dilihat dari data perkara Pengadilan Agama Bandung terlihat ada lonjakan perkara dispensasi kawin pada tahun 2019. Dimana pada tahun yang sama juga pemerintah telah mengesahkan Undang-Undang No.16 Tahun 2019 tentang Perkawinan, yang mana peraturan tersebut merupakan hasil revisi dari Undang-Undang No.1 Tahun 1974. Perubahan itu beralasan karena ketentuan umur pada peraturan sebelumnya dirasa mendiskriminasikan perempuan. Dimana pada awalnya perempuan hanya boleh menikah ketika berumur 16 tahun sedangkan laki-laki berumur 19 tahun. Sehingga dalam UU No.16 Tahun 2019 ketentuan itu diubah, perempuan dan laki-laki diperbolehkan menikah apabila umurnya telah mencapai 19 tahun. Tujuan dari penelitian ini adalah untuk mengetahui apa pertimbangan hakim dalam mengabulkan perkara dispensasi nikah di Pengadilan Agama Bandung disaat pemerintah memperketat umur menikah dengan disahkannya UU No.16 Tahun 2019. Penelitian yang penulis lakukan adalah penelitian deskriptif dengan metode penelitian yuridis empiris, data yang bersumber dari laporan perkara dan peraturan mengenai umur menikah dalam UU No.16 Tahun 2019, dengan menggunakan teknik pengumpulan data melalui wawancara dan penelitian pustaka. Hasil dari penelitian ini menunjukan bahwa hakim dengan melihat fakta-fakta yang terjadi dalam persidangan kebanyakan menggunakan pertimbangan kemaslahatan bagi para pihak.